Defending against disparate marine turtle nest predators: nesting success benefits from eradicating invasive feral swine and caging nests from raccoons. Issue 2 (11th November 2014) - Engeman, Richard M.; Addison, David; Griffin, J.C.
Abstract: Nest predation can threaten marine turtle nesting success, and having to address dissimilar predator species complicates nest protection efforts. On Florida's Keewaydin Island predation by raccoons Procyon lotor and invasive feral swine Sus scrofa are disparate, significant threats to marine turtle nests. Using 6 years of nesting data (mostly for loggerhead marine turtles Caretta caretta ) we examined the impacts of swine predation on nests and the benefits of swine eradication, caging nests to protect them from raccoon predation, and the effects of nest caging on swine predation. Nest predation by swine began in mid nesting season 2007, after which swine quickly annihilated all remaining marine turtle nests. During 2005–2010 raccoon predation rates for caged nests (0.7–20.4%) were significantly lower than for uncaged nests (5.6–68.8%) in every year except 2009, when little raccoon predation occurred. The proportions of eggs lost from raccoon-predated nests did not differ between caged and uncaged nests. Caging did not prevent destruction by swine but median survival time for caged nests was 11.5 days longer than for uncaged nests, indicating that caged eggs in nests have a greater chance of hatching before being predated by swine. The financial cost of the eradication of swine greatly outweighed the value of hatchlings lost to swine predation in 2007.